Caleidoscopio : (una mirada sobre la realidad de España y Ecuador, Europa y América Latina en el contexto de la crisis económica) - Pérez Zúñiga, José María, 1973- (Madrid : Dykinson, S.L., 2017)
About the territorial organization and tax systems of Spain and Ecuador.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed March 25, 2019)
Keywords: Spain -- Politics and government -- 21st century; Ecuador -- Politics and government -- 21st century; Spain -- Social conditions -- 21st century; Ecuador -- Social conditions -- 21st century; Taxation -- Spain -- 21st century; Taxation -- Ecuador -- 21st century; Electronic books